Strengthening the Competence of Bendoroto Village Apparatus in the Village Apparatus Examination to Support Government Accountability - Setyowati, Eka; Juniati, Lita; Bintarawati, Santi; Kinasih, Wahyu Kawitaning (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This community service activity demonstrates that the implementation of a Computer Based Test (CBT)-based village apparatus selection system can strengthen public accountability in the administration of village governance. Through an advocacy approach, the mentoring provided by the Waskita Dharma University Community Service Team contributes to encouraging a more transparent, objective, and accountable selection process, from the planning stage to the evaluation of the exam implementation. In addition, strengthening the competency of prospective village apparatus through CBT-based selection also raises awareness of the importance of responsibility and accountability to the community. Experience in Bedoroto Village, Munjungan District, Trenggalek Regency, shows that the use of technology in the village apparatus recruitment process can be a strategic foundation in realizing professional, accountable, and trusted village governance.